The Dynamics Analysis of Development and Basic Principles of Health Insurance in Indonesia - Sri Sulatriningsih; Didin Sunardi; Erlina Puspitaloka Mahadewi (CV. Inara, 2025)
Healthcare insurance in Indonesia is mandated by the 1945 Constitution, Article 34 paragraph 2. The basic principles of health insurance in Indonesia are based on social justice and broad coverage and support the sustainability of an inclusive and equitable health service system. The health insurance system in Indonesia has transformed into Universal Health Coverage (UHC) through the National Health Insurance (JKN) program. Problems that are still obstacles to the effectiveness of the JKN system include slow payment of claims to health facilities, moral hazard, and gaps in the quality of services between health facilities in big cities and remote areas. This study aims to analyze the basic principles and dynamics of the development of the national health insurance system in Indonesia. The method used is a literature study of scientific sources, public policies, and official reports. The results of the study and review indicate that the principles of solidarity, equity, and sustainability are the main foundations in the implementation of JKN. Although coverage has expanded significantly, challenges such as gaps in access to services, imbalances in contributions and financing, and low public understanding of health insurance still need attention.